The Role of Forensic Accounting in Limiting Creative Accounting Practices: Survey Study of the Opinions of a Sample of Professionals and Academics in Sulaymaniyah Governorate - عبدالعزيز سليمان البياتي, غازي; نزار كريم, فريدون (The Scientific Journal of Cihan University– Sulaimaniya, 2023)
The study aims to clarify and identify the nature of Forensic accounting, its basic concepts, identify the practices of creative accounting and its forms, methods and motives for its use, as well as to identify the role of forensic accounting in limiting creative accounting practices. The questionnaire was used as a research tool, as it was distributed to a sample of academics and professionals in Sulaymaniyah Governorate, (384) forms were distributed and (340) were retrieved from that amount (321) forms valid for analysis through the statistical program (SPSS).the research reached a set of conclusions which indicated that there are a relationship between forensic accounting as an independent variable and the limitation of creative accounting practices as a dependent variable, from the conclusions fulfilling, that forensic accounting is a contemporary field in accounting and has a key role in protecting rights or restoring rights to different aspects in the event of violations economic and financial, also creative accounting It is a process of manipulating accounting numbers by taking advantage of opportunities to get rid of compliance with accounting rules, measurement alternatives and disclosure applications, which affects the credibility of the financial statements and is misleading for decision makers. The research recommended the necessity of having legislation that defines the duties of the forensic accountant in each of the courts and in the objection committees in the tax departments, and developing the work of the expert in line with the requirements of forensic accounting. And the need to use forensic accounting in order to prevent phenomena that are considered negative phenomena, such as creative accounting practices to prevent damage to the country's economic system.